PENGARUH PIJAT OKSITOSIN TERHADAP INVOLUSI UTERI PADA IBU POST PARTUM NORMAL DI RUANG KEMUNING RSUD TABANAN - Kurnia, Made Isa Meidriani; Putu Mastiningsih; Ni Made Risna Sumawati (Poltekkes Kemenkes Banjarmasin, 2025)
The postpartum period (puerperium) is a period that begins after the placenta is released and ends when the reproductive organs return to their original state (before pregnancy). Involution or uterine contraction is a process in which the uterus returns to its pre-pregnancy condition with a weight of about 30 grams. This process begins immediately after the placenta is born due to contractions of the smooth muscles of the uterus. The problem of uterine involution is subinvolution. Uterine subinvolution is the process of late uterine return caused by endometrial infection, residual placenta, blood clots, or uterine myoma. Efforts to prevent postpartum hemorrhage can be done since the 3rd and 4th stages of labor by administering oxytocin. This oxytocin hormone plays a very important role in the process of uterine involution. The purpose of this study was to determine the Effect of Oxytocin Massage on uterine involution in normal postpartum mothers in the Kemuning Room of Tabanan Hospital. This study used a Quasi Experiment design method with a Non Equivalent Control Group Design, namely there were two groups. used in this study were 40 respondents, divided into 2 groups. 20 respondents will be used as the intervention group and 20 more respondents will be used as the control group. Data were analyzed using the Wilcoxon and Mann Whitney Tests. The results of the statistical test conducted to compare uterine involution between the control and intervention groups obtained a p value = 0.041 (p <0.05) which means Ho is rejected so that it can be concluded that there is an effect of oxytocin massage on uterine involution in normal postpartum mothers in the Kemuning room of Tabanan Hospital. Based on the results of this study, it is expected that normal postpartum mothers can apply oxytocin massage to prevent bleeding and uterine subinvolution.